2006
DOI: 10.1029/2006jd007337
|View full text |Cite
|
Sign up to set email alerts
|

Steady decline of east Asian monsoon winds, 1969–2000: Evidence from direct ground measurements of wind speed

Abstract: [1] It is commonly believed that greenhouse-gas-induced global warming can weaken the east Asian winter monsoon but strengthen the summer monsoon, because of stronger warming over high-latitude land as compared to low-latitude oceans. In this study, we show that the surface wind speed associated with the east Asian monsoon has significantly weakened in both winter and summer in the recent three decades. From 1969 to 2000, the annual mean wind speed over China has decreased steadily by 28%, and the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
305
4
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(344 citation statements)
references
References 36 publications
33
305
4
2
Order By: Relevance
“…A number of recent studies have reported declines in near-surface observed wind speeds during the past 30-50 years over parts of North America (Klink, 1999;Tuller, 2004;Pryor et al, 2009;Pryor and Ledolter, 2010), China (Xu et al, 2006;Jiang et al, 2010), regions of Europe (Pirazzoli and Tomasin, 2003;Brazdil et al, 2009) and Australia (McVicar et al, 2008). However, converse trends toward increasing wind speeds have been reported over the global oceans (Young et al, 2011).…”
Section: Temporal Trends In Near-surface Wind Speedsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies have reported declines in near-surface observed wind speeds during the past 30-50 years over parts of North America (Klink, 1999;Tuller, 2004;Pryor et al, 2009;Pryor and Ledolter, 2010), China (Xu et al, 2006;Jiang et al, 2010), regions of Europe (Pirazzoli and Tomasin, 2003;Brazdil et al, 2009) and Australia (McVicar et al, 2008). However, converse trends toward increasing wind speeds have been reported over the global oceans (Young et al, 2011).…”
Section: Temporal Trends In Near-surface Wind Speedsmentioning
confidence: 99%
“…We also examine the degree to which variability in nearsurface wind speeds is attributable to variations in the atmospheric circulation as manifest in teleconnection indices. (Xu et al, 2006;Jiang et al, 2010). For every station, a further data quality constraint 2581 is applied: that more than 85% observations are valid in each climatological season of each year.…”
Section: Objectivesmentioning
confidence: 99%
“…As for changes in W , many parts of the world reported to have experienced a deceleration pattern in W such as the one that had occurred in the TRSR during the last 30 to 50 years. For example, please see You et al (2010b), Ren et al (2005aRen et al ( , 2005b, Xu et al (2006), Ko et al (2010), Hobbins (2004), Tuller (2004), and McVicar et al (2008.…”
Section: Temporal Characteristics Of Trsr Climate Changementioning
confidence: 99%
“…For example, the East Asian summer monsoon (EASM) has weakened since the late 1970s, which is characterized by the weakening of the 850 hPa southwesterly winds, southward shift of the 200 hPa jet stream, and increases in sea level pressure over East Asia (Hu 1997;Wang 2001;Guo et al 2003;Hu et al 2003;Wang and Ding 2006;Xu et al 2006). Furthermore, a cooling trend in the upper troposphere and lower stratosphere over East Asia has led to the weakening in the northward progression of southerly monsoon winds over this region Yu and Zhou 2007).…”
Section: Introductionmentioning
confidence: 99%